An Evaluation of the Urban Fringe Landscape Ring: The Case of Łódź, Poland - Tomczak, Anna Aneta; Warsza, Robert (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
The article describes the spatial planning policy carried out in suburban areas that have not yet been subject to urbanisation within the administrative borders of the Polish city of Łódź and in zones located just beyond its administrative border. The aim of the study was to evaluate spatial decisions adopted in the planning documents of towns and municipalities. The evaluation included the peripheral areas around the city of Łódź called the urban fringe landscape ring. The area of the ring was divided into subzones where detailed research was conducted. The current forms of land use were compared with the planned development directions adopted in the planning documents. Breakdowns showing the percentage increase in areas designated to be developed now and in the future, as well as in areas intended for preservation in the form of open spaces, were made. The need to develop new areas was analysed in relation to demographic conditions and area development capacity. Conclusions from the study showed a significant excess of planned investment areas, the deliberate appropriation of open landscapes and a lack of local planning coherence.